The hidden price of free advice: Negotiating the paradoxes of public sector business advising. (May 2021) - Arshed, Norin; Knox, Stephen; Chalmers, Dominic; Matthews, Russell
Business advisors working in publicly funded enterprise agencies encounter a range of tensions as part of their everyday work. These tensions subtly shape how they provide advice and can lead to variability in how enterprise policy is delivered on the ground. We explore the competing demands facing advisors by inductively analysing advice-giving practices in public sector enterprise agencies. We find three overarching drivers of advisor role tension, including institutional demands, client demands and intrinsic demands; additionally, a further seven discrete work tactics advisors deploy to navigate these tensions are analysed. From our findings, we develop a theoretical model that advances a dynamic understanding of public sector business advice. We conclude by reflecting on the structural issues with public sector advising that might constrain the efficacy of advisors.